(untitled) (Journal of Food and Dietetics Research, 2021)
The study was conducted for the assessment of nutritional, functional status and, Quality of Life (QoL) of selected male cancer patients undergoing cancer therapy. A purposive sampling method was adopted and an interview schedule was used to elicit data. The nutritional status assessment was conducted by incorporating modified Subjective Global Assessment (SGA), QoL, and functional status of the patients. The findings suggested that head and neck cancer was the leading type of cancer followed by lung, stomach and oesophagus cancer and a vast majority of patients were in the terminal stages of cancer. The Subjective Global Assessment (SGA) revealed that majority of the patients belonged to mildly-moderately nourished category. Majority study subjects had an inadequate nutrient intake with respect to energy, protein, fat, calcium and iron. A statistically significant difference was observed between the actual and suggested nutrient intake. The mean values of physical, social/family, emotional and functional well-being using the FACT-G scale were computed to be 29,26.5, 24, and 175.5, respectively showing that QoL was poor among study subjects, thus impacting cancer therapy. The assessment of nutritional status and physical, social, emotional and functional well-being in cancer patients is crucial for early detection of malnutrition and poor well-being thus facilitating further deterioration and improving the outcome of cancer therapy.